ผลกระทบของมอนต์มอริลโลไนต์คอลลอยด์ต่อการเคลื่อนตัวของสังกะสีและแคดเมียมในคอลัมน์ทรายอิ่มตัว - อรกช เชาว์โพธิ์ทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
This study investigated the impacts of pH on co-transport of zinc (Zn), cadmium (Cd) and montmorillonite colloids through water-saturated sand column. The Zn-bearing montmorillonites and Zn-Cd-bearing montmorillonites were injected through the column containing saturated sand, which was simulated as a groundwater flowing under a pressure aquifer. There are three column experiments consisting of two columns of Zn at pH 3 and 6, as well as one binary metal (Zn and Cd) column at pH 6. The single metal column used 10 ppm of Zn and binary metal column experiment used mixed solution of Cd (5 ppm) and Zn (5 ppm) with 100 ppm of montmorillonite colloids. The solutions of different pH conditions were pumped to the column in upward mode at a constant velocity of 0.159 cm/min. According to column experiments, as the pH value increases from 3 to 6, it causes an increase of Freundlich constants (KF ) from 3.42 to 3.48 for the equilibrium model (Eq), and increase from 2.46 to 3.01 for the two-site model (TSM). The migration of Zn is decreased with increasing pH from pH 3 to pH 6. In other words, the retardation factor (Rf) increased from 8.85% to 38.69% when the pH increased from 3 to 6. Adsorption of mixed Zn and Cd at pH 6 appeared to be lower than those of the single heavy metal columns. For Zn, KF decreased from 3.01 to 2.62, while KF of Cd decreased from 3.14 to 2.32. Thus, the montmorillonite colloids facilitates the migration of Zn and Cd in the mixed system faster than those of each individual Zn and Cd.